2017
DOI: 10.1080/17290376.2017.1387598
|View full text |Cite
|
Sign up to set email alerts
|

Modelling self-assessed vulnerability to HIV and its associated factors in a HIV-burdened country

Abstract: Background: Globally, individuals’ self-assessment of vulnerability to HIV infection is important to maintain safer sexual behaviour and reduce risky behaviours. However, determinants of self-perceived risk of HIV infection are not well documented and differ. We assessed the level of self-perceived vulnerability to HIV infection in Nigeria and also identified its risk factors. Methods: We explored a recent nationally representative data with self-reported vulnerability (‘high’, ‘low’ and ‘no risk at all’) to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…The association between knowledge of HIV and HIV infection has been found to be inconsistent from several reports in different parts of the world. While some authors have documented having good knowledge of HIV does not translate to positive behavioural change and low HIV prevalence (Fagbamigbe et al, 2017;Gobopamang, 2011), others documented that poor knowledge of HIV transmission routes to be a risk factor for HIV infection (Hong et al, 2012). In the present study, the odds of HIV infection was higher among clients not informed of the routes of HIV transmission, prevention of HIV transmission and clients with poor knowledge of HIV.…”
Section: Discussioncontrasting
confidence: 60%
“…The association between knowledge of HIV and HIV infection has been found to be inconsistent from several reports in different parts of the world. While some authors have documented having good knowledge of HIV does not translate to positive behavioural change and low HIV prevalence (Fagbamigbe et al, 2017;Gobopamang, 2011), others documented that poor knowledge of HIV transmission routes to be a risk factor for HIV infection (Hong et al, 2012). In the present study, the odds of HIV infection was higher among clients not informed of the routes of HIV transmission, prevention of HIV transmission and clients with poor knowledge of HIV.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the concept of vulnerability has been investigated in numerous studies (Ayres et al, 2006;Fagbamigbe et al, 2017;Mahapatra et al, 2018;Queiroz et al, 2019), only one study has investigated the association between the three dimensions and level of knowledge about STIs (Gomes et al, 2017). Moreover, no such investigation has been carried out in populations of subnormal agglomerates in urban areas in Brazil, particularly the Brazilian Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…When people have a perception (correct or incorrect) of their partner's faithfulness, this is likely to influence their sexual and reproductive behaviour and practices. In fact, studies have found evidence of a significant association between the perception of partner unfaithfulness and having multiple sexual partnerships (Steffenson et al, 2011;Cox et al, 2014;Chialepeh & Sathiyasusuman, 2015;Kenyon et al, 2016), and negative outcomes such as STIs (Fishbein et al, 2004;Fagbamigbe et al, 2017) and HIV infection (Mishra, 2009;Mah & Shelton, 2011). As for a more specific case, Mishra et al (2009) found a significant inverse association between level of partner faithfulness and HIV infection among cohabiting couples in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Norms about partner faithfulness can be quite different in different social contexts or social circles (Young, 2005), but generally most such norms prescribe actors to exchange truthful information regarding the kind of social and sexual life they have (Whisman & Snyder, 2007;Parker, 2009). Moreover, several studies in sub-Saharan Africa have shown that infidelity has negative social consequences such as risky sexual behaviours, broken trust and even divorce (Cox et al, 2014;Kenyon et al, 2016;Fagbamigbe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%